(untitled) (Al-Academy, 2024)
A series of challenges that cannot be sustained puts people in a dilemma between many minorities and risks combined with today’s uses. The matter was not specifically resolved in daily life. This study investigated the dispute between the sustainability of the green economy and the environment by comparing the use of single-use plastic water jugs and common bottles between two different age groups. In order to achieve the goal of the study and address the research problem, the study followed the two descriptive and analytical approaches, by presenting previous studies that dealt with some of the difficulties of using plastic water bottles, as we mentioned previously, and the applied approach to conduct an analytical study of more than one design of the existing bottles in the market and proposed (the new design), specifications, and extent of ease. The use of each package and does it meet the user’s needs or not? And also the experimental approach to setting some design standards in designing the new packaging itself or the tools that help in this purpose. The study was carried out through the results of the questionnaire that was distributed to a group that responded to the experiment, consisting of 72 people as a random sample of 111 people who were drawn from different age groups of both sexes (males and females), meaning a response rate of approximately 65%. The results showed that the proposed model achieved different rates of differences in Distribution locations are among the goals and elements of improving user experience. The results of the study confirm the dissatisfaction with much of the design of plastic bottles among some users in some groups, such as the elderly, and the specification of certain features of the bottle to enhance the ability to open the bottle, carry it, or move around with it so that it is sufficient for the amount of bottled water. Furthermore, this study highlights the shift from the selective, efficiency-oriented approach of the linear economy to the integrated circular economy that focuses on efficiency to compensate for the negative impacts of the preferred bottle option on the environment and support older people. The study concluded with recommendations, the most important of which is that the industry and design community should identify that support the coexistence of humans and nature on Earth through an exploratory perspective and remove barriers, such as industrial inertia. As product developers and designers, we still have the ability to bridge the gaps between traditional policies, environmental imperatives, and challenges associated with the difficulty of using such a product (plastic water bottles) to create a better future for people surrounded by different products, especially the elderly